Presumed innocent [videorecording (DVD)] - Pakula, Alan J., 1928-1998; Ford, Harrison, 1942-; Dennehy, Brian; Julia, Raul; Bedelia, Bonnie, 1946-; Turow, Scott (Warner Home Video, 1997)
Rusty Sabich's been swept up in an obsessive affair with a coworker in the prosecutor's office. When she is murdered, he's asked to lead the investigation. Then, astonishingly, he's accused of the crime. He's the perfect suspect and his fight to clear his name pulls him into a whirlpool of lies and secrets.